2020
DOI: 10.1186/s13054-020-03417-0
|View full text |Cite|
|
Sign up to set email alerts
|

Risks of ventilator-associated pneumonia and invasive pulmonary aspergillosis in patients with viral acute respiratory distress syndrome related or not to Coronavirus 19 disease

Abstract: Background Data on incidence of ventilator-associated pneumonia (VAP) and invasive pulmonary aspergillosis in patients with severe SARS-CoV-2 infection are limited. Methods We conducted a monocenter retrospective study comparing the incidence of VAP and invasive aspergillosis between patients with COVID-19-related acute respiratory distress syndrome (C-ARDS) and those with non-SARS-CoV-2 viral ARDS (NC-ARDS). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
95
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 46 publications
18
95
2
3
Order By: Relevance
“…Therefore, since some patients may have experienced more than one VAP episode, we also cannot exclude an underestimation of the true incidence rate of VAP in critically ill COVID-19 patients. With regard to organisms isolated from deep respiratory specimens in patients with VAP in our series, the higher frequency of Gram-negative bacteria we registered is in line with recent data from other countries [ 22 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, since some patients may have experienced more than one VAP episode, we also cannot exclude an underestimation of the true incidence rate of VAP in critically ill COVID-19 patients. With regard to organisms isolated from deep respiratory specimens in patients with VAP in our series, the higher frequency of Gram-negative bacteria we registered is in line with recent data from other countries [ 22 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Significant disparities exist in the epidemiology of VAP, arguing for a standardization of definitions. Blonz et al, reported a crude incidence rate of 48.9% [ 1 ] in agreement with incidence rates ranging from 48 to 79% [ 3 – 6 ] in other cohorts. This rate contrasts substantially with the 29% observed in a multicenter study performed during the first COVID-19 wave in Italy [ 7 ].…”
supporting
confidence: 66%
“…The majority of VAPs were diagnosed based on bacteriological analysis from endotracheal aspirates (42.6%) in the study by Blonz et al, similar to the methods chosen by others [ 6 ]. Bronchoalveolar lavage (BAL) accounted for a quarter of sampling technique in COVID-ARDS patients, compared to 60% in non-COVID ARDS, in one study [ 3 ]. Importantly, quantitative distal as well as proximal samples were performed, but some authors only considered distal samples [ 3 , 4 ], and others also included molecular methods [ 5 , 9 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have already reported various frequency rates of ICU-acquired pneumonia in mechanically ventilated COVID-19 patients, with estimated incidence ranging from 16 to 31% in two early reports from China [11,12]. Since then, several studies confirmed this impression [13][14][15][16]. Importantly, an accurate estimation for the cumulative risk of ICU-acquired pneumonia in ventilated patient requires handling two main competing events that are extubation and death to avoid misinterpretation of risks.…”
Section: Icu-acquired Infections In Covid-19 and Non-covid-19 Patientsmentioning
confidence: 99%